2020
DOI: 10.36740/wlek202003115
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Syndromes of the Thalamic Stroke In the Classical Vascular Territories: A Prospective Hospital-Based Cohort Study

Abstract: The aim: We aimed to determine, describe, and analyze the clinical and neuroimaging features of vascular syndromes of acute thalamic stroke in the classical vascular territories in a prospective hospital-based cohort study. Materials and methods: We have prospectively recruited 319 acute stroke patients, admitted to the Neurological Center at an academic hospital (Oleksandrivska Clinical Hospital) in Kyiv, Ukraine. Complex neurological, clinical, laboratory, ultrasound, and neuroimaging examinations were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Contrary to our results, in a small cohort of 9 patients with acute inferolateral thalamic stroke, which however spread to the internal capsule in most patients, ⁓45% showed symptoms of longing, apathy, and fear. Patients with anterior thalamic stroke were not included in this earlier study ( Prokopiv and Fartushna, 2020 ). Based on our and previous studies together with anatomical evidence, it can be concluded that the anterior thalamic nuclei play a role in emotion processing, most likely by connecting the anterior thalamus to the limbic system via the cingulate cortex and entorhinal cortex, the so-called medial limbic loop ( Schmahmann, 2003 ; Chen et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to our results, in a small cohort of 9 patients with acute inferolateral thalamic stroke, which however spread to the internal capsule in most patients, ⁓45% showed symptoms of longing, apathy, and fear. Patients with anterior thalamic stroke were not included in this earlier study ( Prokopiv and Fartushna, 2020 ). Based on our and previous studies together with anatomical evidence, it can be concluded that the anterior thalamic nuclei play a role in emotion processing, most likely by connecting the anterior thalamus to the limbic system via the cingulate cortex and entorhinal cortex, the so-called medial limbic loop ( Schmahmann, 2003 ; Chen et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort study, patients with chronic inferolateral thalamic stroke revealed increased anxiety and reduced quality of life comprising mental and physical health ( Liebermann et al, 2013 ), however with very heterogeneous timing of examinations (37.2 ± 28.4 months post-stroke). In a small cohort of 9 patients with acute inferolateral thalamic stroke, which however spread to the internal capsule in most patients, ⁓45% showed symptoms of longing, apathy, and fear ( Prokopiv and Fartushna, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The work is a part of the posterior circulation stroke study. Its settings, parents, definitions, inclusion, and exclusion criteria have been reported in detail previously [12][13][14][15][16][17][18][19][20][21].…”
Section: Methodsmentioning
confidence: 99%
“…The study settings, patterns, definitions, inclusion, and exclusion criteria have been reported in detail previously [16][17][18][19][20][21][22][23][24]. Briefly, 120 patients with MRI-positive acute posterior circulation stroke were consecutively selected.…”
Section: Methodsmentioning
confidence: 99%